An evaluation of apalutamide for the treatment of prostate cancer. (1st September 2020) - Boukovala, Myrto; Spetsieris, Nicholas; Efstathiou, Eleni
ABSTRACT: Introduction: Novel androgen signaling inhibitors are currently standard of care in the treatment of patients with prostate cancer. Second-generation androgen receptor antagonists have demonstrated efficacy in earlier disease settings, fulfilling an unmet need in the treatment of patients with advanced prostate cancer. Areas covered: The present article focuses on the development and establishment of apalutamide among the available treatment options for prostate cancer. A literature search was performed in Pubmed/Medline for past studies and reviews of the drug. Ongoing clinical trials were also examined in the Clinicaltrials.gov online database. Expert opinion: Apalutamide has demonstrated benefit for patients with non-metastatic castration resistant and metastatic hormone naive prostate cancer. It is an efficacious, tolerable, and convenient oral agent, thus a valuable addition in the armamentarium of prostate cancer therapeutics for both non-metastatic castrate resistant and metastatic hormone naïve prostate cancer. Ongoing trials are investigating the drug as monotherapy and in combinations in other disease settings. Results are expected to further expand the drug's indications and shape the future landscape of prostate cancer therapy.